2005
DOI: 10.1007/s00280-005-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase I combination chemotherapy study of biweekly paclitaxel and S-1 administration in patients with advanced gastric cancer

Abstract: The aim of the current study was to determine the maximum tolerated dose (MTD) and the dose limiting toxicity (DLT) of a combination of paclitaxel and S-1 in patients with advanced gastric cancer. Fifteen patients were enrolled. The dose for S-1 was set at 80 mg/m2/day (days 1-14), while the dose for paclitaxel increased by 10 mg/m2 for every three patients, with a starting dose of 100 mg/m2 and was given biweekly on day 1 and 15. There was no severe toxicity (grade 4) recorded in patients receiving up to 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The incidences of grades 3 and 4 toxic effects in our study are consistent with those reported previously for the same S-1 combination regimen (Ajani et al, 2006b;Inokuchi et al, 2006). When paclitaxel was administered every 3 weeks with or without 5-FU, non-haematological toxicity, apart from alopecia of grade 3 or higher, included neuropathy (0 -29%), myalgia (0 -27%), and nausea/vomiting (0 -7%) Yamada et al, 2001;Arai et al, 2003;Hokita et al, 2005;Kondo et al, 2005;Inokuchi et al, 2006). Although there are limitations in comparing the results of different studies because of differences in factors such as the dose and treatment schedule of paclitaxel therapy and the extent of prior treatment, neuromuscular toxicity, the most common adverse effect of paclitaxel, was very mild in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidences of grades 3 and 4 toxic effects in our study are consistent with those reported previously for the same S-1 combination regimen (Ajani et al, 2006b;Inokuchi et al, 2006). When paclitaxel was administered every 3 weeks with or without 5-FU, non-haematological toxicity, apart from alopecia of grade 3 or higher, included neuropathy (0 -29%), myalgia (0 -27%), and nausea/vomiting (0 -7%) Yamada et al, 2001;Arai et al, 2003;Hokita et al, 2005;Kondo et al, 2005;Inokuchi et al, 2006). Although there are limitations in comparing the results of different studies because of differences in factors such as the dose and treatment schedule of paclitaxel therapy and the extent of prior treatment, neuromuscular toxicity, the most common adverse effect of paclitaxel, was very mild in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In 2005, Hokita et al (2005) reported the results of a phase I study of S-1 combined with paclitaxel in patients with advanced gastric cancer. The response rate was 53%, and the MST was 428 days.…”
Section: Discussionmentioning
confidence: 99%
“…In Korean trial, the dose was Wnely adjusted compared with Japanese trials in which S-1 dose by body surface area (BSA) was roughly divided into three levels. The actual dose was nearly same in patients with BSA between 1.4-1.7 m 2 of two nations paclitaxel 50-60 mg/m 2 , weekly [6,7,9,13,17,20,23]. The most common dose limiting toxicities were grade 3 diarrhea or grade 4 neutropenia.…”
Section: Time (Weeks)mentioning
confidence: 95%
“…Paclitaxel has synergistic antitumor eVects with 5-Xuorouracil (5-FU) according to clinical trials as well as preclinical studies, and a diVerent spectrum of side eVects [12,18]. Several clinical trials of S-1 and paclitaxel combination therapy have been conducted in Japan [6,7,9,13,17,20,23]. The response rate has been reported to be 40-60% with the schedule of S-1 80 mg/m 2 for 14 days plus weekly paclitaxel 50-60 mg/m 2 on days 1 and 8.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials of S-1 and paclitaxel combination therapy have been conducted in Japan [28][29][30][31][32][33]. The response rate has been reported to be 40%-60% with the schedule of S-1 80 mg/m 2 for 14 days plus paclitaxel 50-60 mg/m 2 on days 1 and 8 or days 1 and 15.…”
Section: Introductionmentioning
confidence: 99%